2015
DOI: 10.1371/journal.pone.0121035
|View full text |Cite
|
Sign up to set email alerts
|

Eye-Head Coordination for Visual Cognitive Processing

Abstract: We investigated coordinated movements between the eyes and head (“eye-head coordination”) in relation to vision for action. Several studies have measured eye and head movements during a single gaze shift, focusing on the mechanisms of motor control during eye-head coordination. However, in everyday life, gaze shifts occur sequentially and are accompanied by movements of the head and body. Under such conditions, visual cognitive processing influences eye movements and might also influence eye-head coordination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
63
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(70 citation statements)
references
References 43 publications
7
63
0
Order By: Relevance
“…Taken together our results are compatible with the control models for manipulative tasks (Johansson and Edin 1993; Randall Flanagan et al 2006; Johansson and Flanagan 2009; Fang et al 2015; Haruno et al 2001; Flanagan and Wing 1997). In the first experiment, we observed that passers endowed with both visual and haptic/tactile input use predictive/anticipatory control purely based on vision to trigger the handover (Figs.…”
Section: Discussionsupporting
confidence: 90%
“…Taken together our results are compatible with the control models for manipulative tasks (Johansson and Edin 1993; Randall Flanagan et al 2006; Johansson and Flanagan 2009; Fang et al 2015; Haruno et al 2001; Flanagan and Wing 1997). In the first experiment, we observed that passers endowed with both visual and haptic/tactile input use predictive/anticipatory control purely based on vision to trigger the handover (Figs.…”
Section: Discussionsupporting
confidence: 90%
“…The results show that head direction and saccade direction are closely aligned when they occur at the same time (panel a), but are increasingly divergent as time progresses (panel c-d). This suggests that gaze and head have different characteristics, reflecting different roles in visual exploration, a result that confirms similar findings ofFang et al (2015) andSolman et al (2017).…”
supporting
confidence: 82%
“…It was shown that sighted observers perform several saccades per head movement that are not always in the same direction as the head movement. 28 There are also many factors that affect eye-head coordination in real-world gaze behavior, 29 including external factors such as irregularity of the terrain. 30 Involuntary eye movements, even when users have been trained to keep their eyes straight, introduce localization error.…”
Section: Discussionmentioning
confidence: 99%